Penyuluhan dan Simulasi Pertolongan Pertama pada Balita di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deliserdang Provinsi Sumatera Utara Tahun 2024 - Yesica G Sianipar; Friza N S Situmorang; Magdalena Barus; Rismalia Tarigan; Efryanti K Pakpahan; Elni Arizona Hutagaol (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Choking is a condition where the upper airways are blocked by food or other objects which causes breathing problems. This is a medical emergency that can occur suddenly, and requires immediate action by anyone who is near the victim, because if left too long the body can experience a lack of oxygen (hypoxia) and resulting in death. Choking is a respiratory condition that is often underestimated by society. In children, the cause of choking is not chewing food properly and eating too much at one time. Apart from that, children also often put small solid objects into their mouths.Treatment is usually successful and the survival rate can reach 95%. Early treatment for choking is divided into 3 types, namely back blow (patting on the back), abdominal thrust (stomping on the stomach) also known as the Heimich maneuver and chest thrust (stomping on the chest).